The Effectiveness of Serious Games in Improving Memory Among Older Adults With Cognitive Impairment: Systematic Review and Meta-analysis - Alaa Abd-alrazaq; Dari Alhuwail; Eiman Al-Jafar; Arfan Ahmed; Farag Shuweihdi; Shuja Mohd Reagu; Mowafa Househ (JMIR Publications, 2022)
BackgroundMemory, one of the main cognitive functions, is known to decline with age. Serious games have been used for improving memory in older adults. The effectiveness of serious games in improving memory has been assessed by many studies. To draw definitive conclusions about the effectiveness of serious games, the findings of these studies need to be pooled and aggregated. ObjectiveThis study aimed to assess the effectiveness of serious games in improving memory in older adults with cognitive impairment. MethodsA systematic review of randomized controlled trials was carried out. The search sources included 8 databases, the reference lists of the included studies and relevant reviews, and the studies that cited the included studies. In total, 2 reviewers (AA and MH) independently carried out the study selection, data extraction, risk of bias assessment, and quality of evidence appraisal. Extracted data were synthesized using a narrative approach and a statistical approach (ie, multilevel meta-analysis), as appropriate. ResultsOf the 618 citations retrieved, 18 (2.9%) met the eligibility criteria for this review. Of these 18 studies, 15 (83%) randomized controlled trials were included in 10 multilevel meta-analyses. We found that serious games were more effective than no or passive interventions in improving nonverbal memory (P=.02; standardized mean difference [SMD]=0.46, 95% CI 0.09-0.83) and working memory (P=.04; SMD=0.31, 95% CI 0.01-0.60) but not verbal memory (P=.13; SMD=0.39, 95% CI −0.11 to 0.89). The review also showed that serious games were more effective than conventional exercises in improving verbal memory (P=.003; SMD=0.46, 95% CI 0.16-0.77) but not nonverbal memory (P=.30; SMD=−0.19, 95% CI −0.54 to 0.17) or working memory (P=.99; SMD=0.00, 95% CI −0.45 to 0.45). Serious games were as effective as conventional cognitive activities in improving verbal memory (P=.14; SMD=0.66, 95% CI −0.21 to 1.54), nonverbal memory (P=.94; SMD=−0.01, 95% CI −0.32 to 0.30), and working memory (P=.08; SMD=0.37, 95% CI −0.05 to 0.78) among older adults with cognitive impairment. Finally, the effect of adaptive serious games on working memory was comparable with that of nonadaptive serious games (P=.08; SMD=0.18, 95% CI −0.02 to 0.37). ConclusionsSerious games have the potential to improve verbal, nonverbal, and working memory in older adults with cognitive impairment. However, our findings should be interpreted cautiously given that most meta-analyses were based on a few studies (≤3) and judged to have a low quality of evidence. Therefore, serious games should be offered as a supplement to existing proven and safe interventions rather than as a complete substitute until further, more robust evidence is available. Future studies should investigate the short- and long-term effects of serious games on memory and other cognitive abilities among people of different age groups with or without cognitive impairment.